(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Lexical economy, the principle of conveying maximum meaning with minimal linguistic resources, is a universal feature of language, yet its expression varies across typologically distinct languages. This study compares how English, an analytic language, and Uzbek, an agglutinative language, employ stylistic devices—ellipsis, metaphor, metonymy, synecdoche, and phraseological units—to achieve lexical economy. Through qualitative analysis of literary texts, media discourse, spoken language, and digital communication, we identify shared and distinct strategies, such as English’s reliance on syntactic brevity and clipping versus Uzbek’s use of affixation and proverbs. Findings reveal that both languages leverage universal cognitive principles, but cultural and structural factors shape device choice. This research advances comparative linguistics, offering insights for translation, education, and multilingual discourse analysis.